The Study of Site Selections of Green Open Space as a City Park in the Badung Regency - Putra, Putu Andre Wicaksana; Sueca, Ngakan Putu; Prajnawrdhi, Tri Anggraini (Journal of A Sustainable Global South, 2020)
The density of a city affects the power to build an area. Regional development has a large impact on compaction and land cover on an area. This will certainly affect the reduced availability of open land, especially green open space (GOS) in an area. At the mandate of the government through Law No. 26 of 2007 concerning spatial planning it is required that within an area the availability of green open space be 30% of the total area. Badung Regency need for green space with a minimum area standard / capita of 0.3 m2 will obtain the area of ??green park needs of the City of 18,900 m2. The need for green space is then initiated by the Government of Badung Regency that the procurement will be followed by the provision of public space functions in the form of city parks. In the provision of green space in the form of city parks, a study of locations that will be used as city parks is needed. This location study begins by looking at locations that have potential by looking at accessibility, social, cultural, economic, and physical conditions as well as permits and regulations related to the land status. Therefore, it is deemed necessary to conduct a site study using the Analytical Hierarchy Process (AHP) method. That way it will be easier to conclude and determine the best location as a function of green open space as well as public open space in the form of city parks. Keywords : Location, Green Open Space, City Park, Mangupura